Development of Theater Education Textbook with Character Education and Local Wisdom Through Active Learning to Improve the Students’ Script Writing Ability - Ismail, Muh.; Winarni, Retno (VNU Journal of Science: Education Research, 2019)
The purposes of this study are to describe: (1) the students’ and lecturers’ needs on the Theater Education Textbook, (2) the development of the textbook model, (3) the effectiveness testing on the designed textbook, and (4) the result of the textbook dissemination. This research was Research and Development using Borg and Gall’s framework that consisted of 4 stages: (1) exploration, (2) model development, (3) model testing, and (4) dissemination. The research approach used in the exploration stage was a qualitative descriptive approach. The data were collected through documentation study, observation, in-depth interview, and questionnaire. The data were then analyzed by using interactive analysis model. Model testing was done by experimental research. The results of this research were: (1) the exploration stage showed that the Theater Education Textbook used in Undergraduate Elementary Teacher Education (ETE) Program of Sebelas Maret University, Muhammadiyah University, and Slamet Riyadi University Surakarta did not meet the students’ and lecturers’ needs, (2) the theater education textbook was developed through preliminary field testing; and (3) testing phase of textbook effectiveness was done through main field testing. The value of t-obtained is 0.17 and t-table (0.05; 173) = 1.64. Thus, the critical area {t <-1.64 or t> 1.64}. Since t-obtained (0.17) < t-table (1.64) H0: μ1 ≠ μ2 was accepted. This means that the theater script writing textbook with character education and local wisdom was able to improve the students’ scriptwriting ability.